High-performance lithium iron phosphate cathode material and preparation method thereof

CN120622444BActive Publication Date: 2026-10-09HUBEI XINGFA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510810298.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2026-10-09
Estimated Expiration
2045-06-17

AI Technical Summary

Technical Problem

[0004]本发明目的在于提供一种高性能磷酸铁锂正极材料及其制备方法,以解决现有技术中磷酸铁锂作为锂离子电池材料性能无法满足现有市场需求这一问题

Benefits of technology

(1)采用溶剂热法制备出羟基磷酸铁锂前驱体,该羟基磷酸铁锂前驱体颗粒粒径为200-400 nm,且颗粒大小分布均匀,保证了后端磷酸铁锂的颗粒均一性,缩短锂离子传输路径,提高其电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120622444B_ABST
    Figure CN120622444B_ABST
Patent Text Reader

Abstract

The application provides a high-performance lithium iron phosphate positive material and a preparation method thereof. The application comprises the following steps: mixing, stirring and uniformly mixing a lithium source, a phosphorus source, an iron source and a dopant, then transferring to a high-pressure reaction kettle for high-temperature and high-pressure reaction, cooling to room temperature after the reaction, and then performing suction filtration, washing and drying on the precipitate to obtain a lithium iron hydroxyphosphate precursor; mixing, sand milling, spray drying, sintering and crushing the lithium iron hydroxyphosphate, a carbon source and polyethylene glycol diglycidyl ether to obtain a uniform carbon-coated lithium iron phosphate positive material. The lithium iron hydroxyphosphate precursor prepared by the hydrothermal method is first used, then the epoxy ring-opening cross-linking reaction of polyethylene glycol diglycidyl ether and the hydroxyl group of the lithium iron hydroxyphosphate is used to prepare the lithium iron phosphate / carbon positive material with uniform particle size and uniform carbon layer, so that the electrochemical performance of the lithium iron phosphate material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium iron phosphate material preparation technology for lithium-ion battery cathode materials, specifically relating to a high-performance lithium iron phosphate cathode material and its preparation method. Background Technology

[0002] Lithium iron phosphate (LiFePO4) cathode materials with an olivine structure are widely used in electric vehicles and energy storage systems due to their excellent thermal stability and long cycle life. However, with technological advancements and market demands, the performance requirements for lithium iron phosphate are constantly increasing.

[0003] To improve the performance of lithium iron phosphate (LFP) and further expand its application areas to meet the growing daily energy demand, modifications are mainly focused on accelerating the lithium-ion diffusion rate and improving electronic conductivity. The most effective methods to accelerate the lithium-ion diffusion rate are particle nano-sizing and ion doping. Particle nano-sizing can shorten the lithium-ion diffusion path and increase diffusion channels, thereby improving the lithium-ion diffusion rate. Ion doping, on the other hand, creates lattice defects, providing more channels for lithium-ion diffusion. Carbon coating technology involves coating the surface of LFP with a layer of carbon material, forming a rich conductive network, thereby enhancing electron conduction between particles. However, existing carbon coating technologies suffer from uneven and discontinuous carbon coating, which affects the electrochemical performance of LFP. Summary of the Invention

[0004] The purpose of this invention is to provide a high-performance lithium iron phosphate cathode material and its preparation method, so as to solve the problem that the performance of lithium iron phosphate as a lithium-ion battery material in the prior art cannot meet the current market demand.

[0005] The technical solution of the present invention is as follows: A method for preparing a high-performance lithium iron phosphate cathode material includes the following steps: S1: Add phosphorus source, iron source, lithium source and dopant to deionized water and stir until homogeneous to obtain solution A.

[0006] S2: Transfer solution A to a high-temperature and high-pressure reactor. After reacting at high temperature for a certain time, suspension B is obtained. Suspension B is then filtered, washed, and dried to obtain lithium iron phosphate precursor.

[0007] S3: Lithium iron phosphate, carbon source and polyethylene glycol diglycidyl ether are added to deionized water to obtain C mixture. The C mixture is ground using a sand mill to obtain lithium iron phosphate slurry. The lithium iron phosphate slurry is spray dried, calcined under an inert atmosphere and pulverized to finally obtain high-performance LFP / C cathode material.

[0008] In step S1, the phosphorus source includes one of H3PO4, FePO4•2H2O, and FePO4•4H2O; the iron source includes one of FeSO4•2H2O, FeSO4•7H2O, FeSO4•5H2O, FePO4•2H2O, and FePO4•4H2O; the lithium source includes one of LiOH•H2O, Li(CH3COO)•2H2O, and lithium citrate; and the dopant is one or more of titanium dioxide, titanium carbide, and ammonium metavanadate. The molar ratio of the phosphorus source, iron source, and lithium source is 1.0-1.05:1.0:1.5-2.0; the molar ratio of the dopant to the iron source is (0.04-0.08):1; the weight of the deionized water accounts for 90%-95% of the total weight of the solution; and the stirring is magnetic stirring for 0.4-0.8 h.

[0009] In step S2, the high-temperature reaction temperature is 150-200 ℃, the reaction time is 24-56 h, the drying temperature is 60-100 ℃, and the particle size of the prepared lithium iron phosphate is 200-400 nm.

[0010] In step S3, the carbon source is one or more of glucose, sucrose, and starch. The molar ratio of lithium iron phosphate to carbon source is 1:0.2-0.4; the amount of polyethylene glycol diglycidyl ether added is 3%-8% of the mass of the lithium iron phosphate added. The n in the molecular formula of polyethylene glycol diglycidyl ether is 2000-6000, preferably one of 2000, 4000, and 6000. The sintering temperature is 500-700 ℃, the heating rate is 2-5 ℃ / min, the holding time is 8-12 h, and the protective atmosphere is one of N2 and Ar.

[0011] .

[0012] The application of the high-performance lithium iron phosphate cathode material is mainly in lithium-ion battery cathode materials and the batteries and devices assembled from them.

[0013] The beneficial effects of this invention are as follows: (1) A hydroxyl lithium iron phosphate precursor was prepared by a solvothermal method. The particle size of the hydroxyl lithium iron phosphate precursor was 200-400 nm and the particle size distribution was uniform, which ensured the uniformity of the downstream lithium iron phosphate particles, shortened the lithium ion transport path, and improved its electrochemical performance.

[0014] (2) Polyethylene glycol diglycidyl ether, as a carbon source, has good hydrophilicity. Its long molecular chains extend to the surrounding particles, preventing the particles from getting close to each other and agglomerating, thus forming well-dispersed nanoparticles. At the same time, its ether group undergoes an epoxy ring-opening reaction with the hydroxyl group of lithium iron phosphate to form a uniform and stable conductive network carbon structure, ensuring the uniformity of carbon coating, thereby improving the electronic conductivity of the material, reducing the internal resistance of the material, and improving its electrochemical performance. Attached Figure Description

[0015] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 The image shows a SEM image of the high-performance lithium iron phosphate prepared in Example 1.

[0017] Figure 2 The charge-discharge curves of the high-performance lithium iron phosphate prepared in Example 1 are shown.

[0018] Figure 3 SEM image of lithium iron phosphate prepared in Comparative Example 1.

[0019] Figure 4 The charge-discharge curves of lithium iron phosphate prepared for Comparative Example 1 are shown. Specific Implementation The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0021] The process for preparing lithium iron phosphate from the above raw materials is described in the following examples: Example 1 A1: Take LiOH•H2O and FePO4•2H2O with a Li / Fe molar ratio of 1.5:1 (LiOH•H2O and FePO4•2H2O are 1.5 mol and 1 mol respectively, and the following steps are prepared according to the molar ratio corresponding to this molar amount), and add titanium dioxide with a Ti / Fe molar ratio of 0.04 to deionized water. The weight of deionized water accounts for 90% of the total mass of the solution. After magnetic stirring for 40 min, a uniformly dispersed suspension is obtained. A2: The suspension obtained in A1 was transferred to a reaction vessel and placed in a muffle furnace (the muffle furnace provides a thermal environment). The reaction was carried out at 150 °C for 48 h to obtain a suspension of lithium iron phosphate. The suspension was washed five times with deionized water and then dried at 80 °C to obtain lithium iron phosphate. A3: The obtained lithium iron phosphate, glucose, and polyethylene glycol diglycidyl ether (n = 2000) were added to deionized water, wherein the Fe / C molar ratio was 1:0.2 (glucose), the amount of polyethylene glycol diglycidyl ether added accounted for 3% of the mass of lithium iron phosphate, and the solid content was adjusted to 38%. The above raw materials were ground and mixed using a sand mill for 30 min, and then the grinding was stopped. The slurry was taken out and spray-dried. The yellow material obtained after spray drying was placed in a tube furnace and heated to 500 ℃ at a heating rate of 2 ℃ / min under a high-purity nitrogen atmosphere, and held for 12 h to obtain high-performance lithium iron phosphate cathode material.

[0022] Example 2 A1: Take Li(CH3COO)•2H2O, H3PO4 and FeSO4•7H2O with a Li / P / Fe molar ratio of 1.55:1.05:1 (specifically, 1.55 mol of Li(CH3COO)•2H2O, 1.05 mol of H3PO4 and 1 mol of FeSO4•7H2O, and the following steps are prepared according to this molar ratio), and add titanium dioxide with a Ti / Fe molar ratio of 0.05 to deionized water, with the weight of deionized water accounting for 92% of the total mass of the solution. After magnetic stirring for 40 min, a uniformly dispersed suspension is obtained. A2: The suspension obtained in A1 was transferred to a reaction vessel and placed in a muffle furnace. The reaction was carried out at 180 °C for 36 h to obtain a suspension of lithium iron phosphate. After washing it five times with deionized water, it was dried at 80 °C to obtain lithium iron phosphate. A3: The obtained lithium iron phosphate, sucrose, and polyethylene glycol diglycidyl ether (n = 6000) were added to deionized water, wherein the Fe / C molar ratio was 1:0.3 (sucrose), the amount of polyethylene glycol diglycidyl ether added accounted for 4% of the mass of lithium iron phosphate, and the solid content was adjusted to 38%. The above raw materials were ground and mixed using a sand mill for 30 min, and then the grinding was stopped. The slurry was taken out and spray-dried. The yellow material obtained after spray drying was placed in a tube furnace and heated to 600 ℃ at a heating rate of 2 ℃ / min under a high-purity nitrogen atmosphere, and held for 10 h to obtain high-performance lithium iron phosphate cathode material.

[0023] Example 3 A1: Take lithium citrate, H3PO4 and FeSO4•5H2O with a Li / P / Fe molar ratio of 2.0:1.03:1 (specifically 2.0 mol lithium citrate, 1.03 mol H3PO4 and 1 mol FeSO4•7H2O, the following steps are prepared according to the molar ratio corresponding to this molar amount), and add ammonium metavanadate with a V / Fe molar ratio of 0.04 to deionized water, the weight of deionized water accounting for 95% of the total mass of the solution. After magnetic stirring for 60 min, a uniformly dispersed suspension is obtained. A2: The suspension obtained in A1 was transferred to a reaction vessel and placed in a muffle furnace. The reaction was carried out at 200 °C for 30 h to obtain a suspension of lithium iron phosphate. After washing it five times with deionized water, it was dried at 80 °C to obtain lithium iron phosphate. A3: The obtained lithium iron phosphate, sucrose, and polyethylene glycol diglycidyl ether (n = 4000) were added to deionized water, wherein the Fe / C molar ratio was 1:0.3 (sucrose), the amount of polyethylene glycol diglycidyl ether added accounted for 6% of the mass of lithium iron phosphate, and the solid content was adjusted to 42%. The above raw materials were ground and mixed using a sand mill for 30 min, and then the grinding was stopped. The slurry was taken out and spray-dried. The yellow material obtained after spray drying was placed in a tube furnace and heated to 700 ℃ at a heating rate of 5 ℃ / min under a high-purity nitrogen atmosphere, and held for 8 h to obtain high-performance lithium iron phosphate cathode material.

[0024] Comparative Example 1 A1: FePO4, LiCO3, glucose, polyethylene glycol, and TiO2 are added to deionized water, wherein the molar ratio of Fe:P:Li is 1:1:1.05 (specifically, 1.0 mol of FePO4 and 1.05 mol of LiCO3, and the following steps are prepared according to this molar ratio), the molar ratio of Ti / Fe is 0.04, the amount of polyethylene glycol added is 3% of the mass of FePO4, and the solid content is adjusted to 40%; the above raw materials are ground and mixed using a sand mill for 30 min, and then the grinding is stopped; the slurry is taken out and spray-dried; the yellow material obtained after spray drying is placed in a tube furnace and heated to 700 ℃ at a heating rate of 2 ℃ / min under a high-purity nitrogen atmosphere to obtain lithium iron phosphate cathode material.

[0025] Comparative Example 2 A1: FePO4, LiCO3, glucose, polyethylene glycol diglycidyl ether, and TiO2 are added to deionized water, wherein the molar ratio of Fe:P:Li is 1:1:1.05 (specifically, 1.0 mol of FePO4 and 1.05 mol of LiCO3, and the following steps are prepared according to this molar ratio), the molar ratio of Ti:Fe is 0.04, the amount of polyethylene glycol diglycidyl ether added is 3% of the mass of FePO4, and the solid content is adjusted to 40%. The above raw materials are ground and mixed using a sand mill for 30 min, and then the grinding is stopped. The slurry is taken out and spray-dried. The yellow material obtained after spray drying is placed in a tube furnace and heated to 700 ℃ at a heating rate of 2 ℃ / min under a high-purity nitrogen atmosphere to obtain lithium iron phosphate cathode material.

[0026] Comparative Example 3 A1: Take LiOH•H2O and FePO4•2H2O with a Li / Fe molar ratio of 1.5:1 (LiOH•H2O and FePO4•2H2O are 1.5 mol and 1 mol respectively, and the following steps are prepared according to the molar ratio corresponding to this molar amount), and add titanium dioxide with a Ti / Fe molar ratio of 0.04 to deionized water. The weight of deionized water accounts for 90% of the total mass of the solution. After magnetic stirring for 40 min, a uniformly dispersed suspension is obtained. A2: The suspension obtained in A1 was transferred to a reaction vessel and placed in a muffle furnace. The reaction was carried out at 150 °C for 48 h to obtain a suspension of lithium iron phosphate. After washing it five times with deionized water, it was dried at 80 °C to obtain lithium iron phosphate. A3: The obtained lithium iron phosphate, glucose, and 1,4-butanediol diglycidyl ether were added to deionized water, wherein the Fe / C molar ratio was 1:0.3 (glucose), and the amount of 1,4-butanediol diglycidyl ether added accounted for 4% of the mass of lithium iron phosphate, and the solid content was adjusted to 38%. The above raw materials were ground and mixed using a sand mill for 30 min, and then the grinding was stopped. The slurry was taken out and spray-dried. The yellow material obtained after spray drying was placed in a tube furnace and heated to 600 ℃ at a heating rate of 2 ℃ / min under a high-purity nitrogen atmosphere, and held for 10 h to obtain high-performance lithium iron phosphate cathode material.

[0027] Comparative Example 4 A1: Take LiOH•H2O and FePO4•2H2O with a Li / Fe molar ratio of 1.5:1 (LiOH•H2O and FePO4•2H2O are 1.5 mol and 1 mol respectively, and the following steps are prepared according to the molar ratio corresponding to this molar amount), and add titanium dioxide with a Ti / Fe molar ratio of 0.04 to deionized water. The weight of deionized water accounts for 90% of the total mass of the solution. After magnetic stirring for 40 min, a uniformly dispersed suspension is obtained. A2: The suspension obtained in A1 was transferred to a reaction vessel and placed in a muffle furnace. The reaction was carried out at 150 °C for 48 h to obtain a suspension of lithium iron phosphate. After washing it five times with deionized water, it was dried at 80 °C to obtain lithium iron phosphate. A3: The obtained lithium iron phosphate, glucose, and polyethylene glycol diglycidyl ether (n = 6000) were added to deionized water, wherein the Fe / C molar ratio was 1:0.4 (glucose), and the amount of polyethylene glycol diglycidyl ether (n = 6000) added accounted for 1% of the mass of lithium iron phosphate, and the solid content was adjusted to 38%. The above raw materials were ground and mixed using a sand mill for 30 min, and then the grinding was stopped. The slurry was taken out and spray-dried. The yellow material obtained after spray drying was placed in a tube furnace and heated to 650 ℃ at a heating rate of 2 ℃ / min under a high-purity nitrogen atmosphere, and held for 10 h to obtain high-performance lithium iron phosphate cathode material.

[0028] Comparative Example 5 A1: Take LiOH•H2O and FePO4•2H2O with a Li / Fe molar ratio of 1.5:1 (LiOH•H2O and FePO4•2H2O are 1.5 mol and 1 mol respectively, and the following steps are prepared according to the molar ratio corresponding to this molar amount), and add titanium dioxide with a Ti / Fe molar ratio of 0.04 to deionized water. The weight of deionized water accounts for 90% of the total mass of the solution. After magnetic stirring for 40 min, a uniformly dispersed suspension is obtained. A2: The suspension obtained in A1 was transferred to a reaction vessel and placed in a muffle furnace. The reaction was carried out at 150 °C for 48 h to obtain a suspension of lithium iron phosphate. After washing it five times with deionized water, it was dried at 80 °C to obtain lithium iron phosphate. A3: The obtained lithium iron phosphate, glucose, and polyethylene glycol diglycidyl ether (n = 2000) were added to deionized water, wherein the Fe / C molar ratio was 1:0.4, and the amount of polyethylene glycol diglycidyl ether (n = 2000) added accounted for 10% of the mass of lithium iron phosphate, and the solid content was adjusted to 38%. The above raw materials were ground and mixed using a sand mill for 30 minutes, and then the grinding was stopped. The slurry was taken out and spray-dried. The yellow material obtained after spray drying was placed in a tube furnace and heated to 700 ℃ at a heating rate of 2 ℃ / min under a high-purity nitrogen atmosphere, and held for 12 h to obtain high-performance lithium iron phosphate cathode material.

[0029] Table 1. Performance comparison between different embodiments and comparative examples

[0030] Table 1 compares the performance of different embodiments and comparative examples. All lithium iron phosphate materials obtained from the embodiments and comparative examples were used as cathode materials to assemble coin cells and pouch cells for testing. Coin cells underwent constant current / constant voltage charging at 0.1C / 0.5C / 1C and constant current discharge tests, with a charging voltage range of 2.5-3.75V. Pouch cells underwent constant current / constant voltage charging at 0.5C and constant current discharge at 0.5C, with a voltage range of 2.5-3.65V. The comparison shows that the embodiments using lithium iron phosphate as a precursor and adding polyethylene glycol diglycidyl ether exhibited higher discharge specific capacity and capacity retention after 2500 cycles compared to the comparative example.

Claims

1. A method for preparing lithium iron phosphate cathode material, characterized in that, The preparation steps include the following: S1: Add phosphorus source, iron source, lithium source and dopant to deionized water and stir until homogeneous to obtain solution A; S2: Transfer solution A to a reaction vessel, and after hydrothermal reaction for a certain time, obtain suspension B. Then, filter, wash and dry suspension B to obtain lithium iron phosphate precursor. S3: Lithium iron phosphate, carbon source and polyethylene glycol diglycidyl ether are added to deionized water to obtain mixture C. The amount of polyethylene glycol diglycidyl ether added is 3%-8% of the mass of lithium iron phosphate. The mixture C is ground using a sand mill to obtain lithium iron phosphate slurry. The lithium iron phosphate slurry is spray dried, calcined under an inert atmosphere and pulverized to finally obtain LFP / C cathode material. The n in the molecular formula of polyethylene glycol diglycidyl ether is 2000-6000. 。 2. The method for preparing lithium iron phosphate cathode material according to claim 1, characterized in that, In step S1, the phosphorus source includes one of H3PO4, FePO4•2H2O, and FePO4•4H2O; the iron source includes one of FeSO4•2H2O, FeSO4•7H2O, FeSO4•5H2O, FePO4•2H2O, and FePO4•4H2O; the lithium source includes one of LiOH•H2O, Li(CH3COO)•2H2O, and lithium citrate; and the dopant is one or more of titanium dioxide, titanium carbide, and ammonium metavanadate.

3. The method for preparing lithium iron phosphate cathode material according to claim 2, characterized in that, In step S1, the molar ratio of the phosphorus source, iron source, and lithium source is 1.0-1.05:1.0:1.5-2.0; the molar ratio of the dopant to the iron source is (0.04-0.08):1; the weight of the deionized water accounts for 90%-95% of the total weight of the solution; the stirring is magnetic stirring, and the stirring time is 0.4-0.8 h.

4. The method for preparing lithium iron phosphate cathode material according to claim 1, characterized in that, In step S2, the high-temperature reaction temperature is 150-200℃, the reaction time is 24-56 h, the drying temperature is 60-100℃, and the particle size of the prepared lithium iron hydroxyphosphate is 200-400 nm.

5. The method for preparing lithium iron phosphate cathode material according to claim 1, characterized in that, In step S3, the carbon source is one or more of glucose, sucrose, and starch, and the molar ratio of lithium iron phosphate to carbon source is 1:0.2-0.4; the solid content is 38%-42%.

6. The method for preparing lithium iron phosphate cathode material according to claim 1, characterized in that, In step S3, n in the molecular formula of polyethylene glycol diglycidyl ether is one of 2000, 4000, or 6000.

7. The method for preparing lithium iron phosphate cathode material according to claim 1, characterized in that, In step S3, the calcination temperature is 500-700 ℃, the heating rate is 2-5 ℃ / min, the holding time is 8-12 h, and the inert atmosphere is either N2 or Ar.

8. A lithium iron phosphate cathode material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 7.

9. The application of the lithium iron phosphate cathode material as described in claim 8 in the preparation of lithium-ion batteries.

Citation Information

Patent Citations

  • Positive electrode composition, positive electrode material and secondary battery

    CN118970054A

  • Carbon-coated lithium iron phosphate active material and preparation method thereof, positive pole piece and lithium battery

    CN119208580A